PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS STEM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA PADA MATERI FISIKA INSTRUMENTASI - Paramita, Ielda; Gustina; Laratu , Wahyuni (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aims to develop STEM-based digital teaching materials to improve students' critical thinking skills in Instrumentation Physics. Development Model The teaching material used is the ADDIE model. The results obtained in this study are that the STEM-based digital teaching materials in the Instrument Physics course are based on the validation results of two digital teaching materials experts which were developed in very good criteria, and are feasible to use. Teaching materials are also assessed as Effective and Practical based on student responses that are in the positive or very good category. STEM-based digital teaching materials on Instrumental Physics Materials are considered to be able to improve students' critical thinking skills, this is indicated by the change in the average value between pre-test and post-test, from 31.32 to 61.60